PROVIDING AIRWORTHINESS OF AIRCRAFTS OF AIRLINE - Кучер, О. Г.; Власенко, П. О. (Science-based technologies, 2009)
The main questions and concepts of providing the necessary level of aircraft airworthiness were analyzed. The structure of airworthiness control on the government level is considered. The speciality of aircraft hard time and on-condition operation were analyzed. The forms of input information, that provide the decision of reliability and flight safety control and analysis tasks were developed. The questions of using aircraft reliability information for providing the necessary airworthiness level were considered.